2020
DOI: 10.1021/acs.jchemed.0c00886
|View full text |Cite
|
Sign up to set email alerts
|

Examination and Improvement of Undergraduate Laboratory Experiment: Thermodynamics of a Surfactant Micellization

Abstract: Thermodynamic characterization of micelle formation from an ionic surfactant in aqueous solutions is a classic experiment in physical chemistry. The critical micelle concentration (CMC) and the degree of micelle ionization (α) can be directly obtained by conductimetry, then thermodynamic parameters (ΔG m o, ΔH m o, ΔS m o) are deduced from the CMC values at different temperatures. Herein, the CMC values at different temperatures were generated by multiple student groups, and the resulting errors were combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The user is strongly suggested to have experience in standard ITC experiments before advancing into the practices described herein. While most educational publications featuring ITC are directed to undergraduate students and describe more basic experiments ,,− or home-built calorimeters, this article is conceptualized for advanced ITC users among graduate students or late-stage undergraduates from the fields of medicinal chemistry, biochemistry, or related disciplines. It is intended to create awareness of typical hindrances and limitations in obtaining reliable data from ITC experiments for medicinal chemistry applications and to help overcome these issues.…”
Section: Introductionmentioning
confidence: 99%
“…The user is strongly suggested to have experience in standard ITC experiments before advancing into the practices described herein. While most educational publications featuring ITC are directed to undergraduate students and describe more basic experiments ,,− or home-built calorimeters, this article is conceptualized for advanced ITC users among graduate students or late-stage undergraduates from the fields of medicinal chemistry, biochemistry, or related disciplines. It is intended to create awareness of typical hindrances and limitations in obtaining reliable data from ITC experiments for medicinal chemistry applications and to help overcome these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reported procedure is cost-effective and easy to execute, it necessitates the use of a computer and image processing software. Zhang et al demonstrated how the thermodynamic parameters are evaluated from the CMC values determined through conductometric and isothermal titration microcalorimetric methods . Antoniades et al disclosed a simple experiment involving surface tension measurements using the “drop weight” method to determine surface excess of surfactants .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al demonstrated how the thermodynamic parameters are evaluated from the CMC values determined through conductometric and isothermal titration microcalorimetric methods. 25 Antoniades et al disclosed a simple experiment involving surface tension measurements using the "drop weight" method to determine surface excess of surfactants. 26 Mansour et al used the concept of tautomerism for the determination of the critical micelle concentration of cetyltrimethylammonium bromide using curcumin as a colored probe.…”
Section: ■ Introductionmentioning
confidence: 99%